PENGARUH PENERAPAN MODEL PROJECT BASED LEARNING TERINTEGRASI STEAM TERHADAP BERPIKIR KREATIF DITINJAU DARI PEMAHAMAN KONSEP FISIKA SISWA SMA PADA MATERI DINAMIKA ROTASI - Rohman, Abd.; Ishafit, Ishafit; Husna, Hotimatul (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
The purpose of this study was to describe the effect of implementing the PjBL model with STEAM on creative thinking based on conceptual understanding of high school students on the rotation dynamics material. The research method used was pre-experiment with one group pretest-posttest design. The population was all class XI IPA odd semester SMA Bustanul Mubtadiin Pangorayan Proppo Pamekasan. The samples were selected by purposive sampling. The research instrument used was a concept understanding test and a creative thinking test. The data in this study were analyzed using two-way ANOVA. The results showed that there was a significant effect on PjBL model integrated with STEAM on creative thinking skills in students of class XI IPA in high school (Fhit = 131,231 α = 0,000 <α = 5%), students who had high concept understanding had the ability to think creatively higher than students who have low concept understanding (Fhit = 123,418 α = 0,000 <α = 5%), there was a very good interaction effect between the STEAM integrated PjBL model and concept understanding on students' creative thinking (Fhit = 4,437 α = 0.042 <α = 5%).